1999
DOI: 10.1300/j083v31n03_08
|View full text |Cite
|
Sign up to set email alerts
|

Client Satisfaction with Transportation and Handyman/Chore Services in a Pilot Shared Cost-Service Coordination Program

Abstract: This descriptive study investigates the validity and reliability of two new instruments to measure client satisfaction with transportation (TSM) and handyman/chore (HSM) services and determines the degree to which clients were satisfied with the transportation and handyman chore services that they received in a pilot cost share program. Reliability testing indicated that both the TSM and the HSM had high internal consistency with respective Chronbach's Alphas of .73 and .77. Validity testing with the TSM (r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These can capture common experiences of services across different settings (e.g., Larsen, Attkisson, Hargreaves, & Nguyen, 1979) or responses to specific services. For ex-ample, Bear and Sauer (1999) have developed reliable measures to assess satisfaction with transport and handyman services for elderly clients.…”
Section: Client Satisfaction and Evaluation Of Social Work Servicesmentioning
confidence: 99%
“…These can capture common experiences of services across different settings (e.g., Larsen, Attkisson, Hargreaves, & Nguyen, 1979) or responses to specific services. For ex-ample, Bear and Sauer (1999) have developed reliable measures to assess satisfaction with transport and handyman services for elderly clients.…”
Section: Client Satisfaction and Evaluation Of Social Work Servicesmentioning
confidence: 99%
“…Preliminary development of satisfaction measures for the remaining CBS of transportation, chore, respite, senior companion, emergency alert, and adult day care began by transforming the semantic differentials that had been developed by Kawabori and Duffin (1978) and the local AAA (Collins & Ferguson, 1992) into the same Likert-type format used with the homemaker, personal care, and home-delivered meals satisfaction instruments. Additional items were added to the CBS scales based on an extensive literature review that identified key components of client satisfaction with each of the different CBS, and two items were added to reflect a cost dimension (Bear & Sauer, 1998). An introductory explanation was also included so that the instruments could be administered over the telephone.…”
Section: Instrument Refinement and Developmentmentioning
confidence: 99%
“…Study of client satisfaction in the area of home health care services has been more extensive. 19,[21][22][23][24][25] Existing research focuses on client satisfaction with home health care services, which usually include the community-based services of homemakers and personal care aides. Tool development has focused on establishing the relevant dimensions and corresponding measurement items of client satisfaction and establishing a measure of reliability and validity.…”
Section: Introductionmentioning
confidence: 99%
“…And, while there is some variation in both the dimensions and items included in the existing measures of satisfaction with home health care services, inclusion of content related to accessibility, convenience, interpersonal characteristics of staff, and service delivery is consistently addressed in each of the home care satisfaction measures reviewed by these researchers. Other dimensions addressed include technical competency, 19,25 cost, 19,21 nursing process 24 and sufficiency. 21 In conclusion, respite care is an important, yet often underused, option in the continuum of long term care services for elders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation